Role of Stress and Smoking as Modifiable Risk Factors for Nonpersistent and Persistent Back Pain in Women. Issue 3 (March 2016) - Schmelzer, Amy C.; Salt, Elizabeth; Wiggins, Amanda; Crofford, Leslie J.; Bush, Heather; Mannino, David M.
Abstract : Objective: The purpose of this study was to examine the association between smoking and stress with nonpersistent and persistent back pain. Materials and Methods: Participants included 3703 women who took part in the Kentucky Women's Health Registry in 2008 and 2011. Multivariate logistic regression modeling was used to examine whether smoking status and stress levels were predictive of nonpersistent and persistent back pain, controlling for sociodemographic characteristics. Results: Stress level was associated with both nonpersistent and persistent back pain, whereas smoking was associated with only persistent back pain. Current smokers were 1.5 times more likely to report persistent back pain compared with never smokers, controlling for age, race, body mass index, educational attainment, and employment status. Women experiencing large or overwhelming amounts of stress were 1.8 times more likely to have nonpersistent back pain and 1.6 times more likely to report persistent back pain, compared with women experiencing small amounts of stress. Discussion: This study further substantiates the findings of prior research that describes a significant relationship between back pain, stress, and smoking. Understanding the role of modifiable risk factors (ie, smoking and stress) and their impact on back pain provides an opportunity to offer a comprehensive and tailored treatment plan.